2017
DOI: 10.1016/j.jms.2016.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Electronic spectroscopy of a cold SiO+ sample: Implications for optical pumping

Abstract: The dispersed fluorescence following pulsed dye laser excitation of the B

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 37 publications
2
18
0
Order By: Relevance
“…Fluorescent measurements showed that ∼97% of the population decays to the X 2 Σ + (ν = 0), ∼3% decays to the X 2 Σ + (ν = 1), and the decay to the A 2 Π state was unobservable. 35 A recent ab initio study further supported these estimates. 37 Inspired by the prospects of the SiO + , we investigated the electronic structure of its isoelectronic analogues To provide an improved estimates of the energies and FCFs, we carried out EOM-IP-CCSD(T)(a)* and EOM-IP-CCSDT calculations of SiO + , SiS + , and SiSe + .…”
Section: R U(r)mentioning
confidence: 77%
See 1 more Smart Citation
“…Fluorescent measurements showed that ∼97% of the population decays to the X 2 Σ + (ν = 0), ∼3% decays to the X 2 Σ + (ν = 1), and the decay to the A 2 Π state was unobservable. 35 A recent ab initio study further supported these estimates. 37 Inspired by the prospects of the SiO + , we investigated the electronic structure of its isoelectronic analogues To provide an improved estimates of the energies and FCFs, we carried out EOM-IP-CCSD(T)(a)* and EOM-IP-CCSDT calculations of SiO + , SiS + , and SiSe + .…”
Section: R U(r)mentioning
confidence: 77%
“…However, the efforts to identify molecular ions suitable for optical cycling have been limited. Odom, Brown, and co-workers have explored optical cycling in AlH + , 30-32 BH + , 33 SiO + , 34,35 and TeH + , 36 often with an eye towards precision measurement. Other molecular ions have been studied theoretically including both cations [37][38][39][40] and anions [41][42][43] .…”
Section: Introductionmentioning
confidence: 99%
“…In order to design a laser cooling scheme for SiO + , accurate knowledge of branching fractions of SiO + radiative relaxation to low lying vibrational and electronic states is necessary. A previous measurement, done by our group, of emission branching factors to high vibrational bands of B 2 Σ + -X 2 Σ + found branching to the (1,0) band at 3% relative to the (0,0) band, while branching to higher vibrational levels and low-lying A 2 Π state could not be detected [24]. We determined that further limits were necessary before we could apply a laser cooling scheme.…”
Section: Introductionmentioning
confidence: 89%
“…Fluorescent measurements showed that ∼97% of the population decays to the X 2 Σ + (ν = 0), ∼3% decays to the X 2 Σ + (ν = 1), and the decay to the A 2 Π state was unobservable. 35 A recent ab initio study further supported these estimates. 37 Inspired by the prospects of the SiO + , we investigated the electronic structure of its isoelectronic analogues While SiO + has been studied in considerable details due to its astrophysical interest and prospects in QIS applications, to 0.9956 in GeSe + .…”
Section: Figmentioning
confidence: 77%